The (Re‐)Appropriation of Spirit Beings – Spirits of the Dead and Spirits of God in a Sepik Community. Issue 1 (1st March 2018) - Falck, Christiane
Abstract : This article explores Nyaura (West Iatmul) ontology and cosmology in the context of religious change. I argue that persisting ontological premises of the Nyaura lifeworld were crucial for the way people appropriated Catholicism and made it their own. I compare my findings to an approach to religious change that has prominently been employed by Joel Robbins before – the notion of humiliation as described in a seminal article by Marshall Sahlins. However, while Robbins argues that a notion of humiliation has led the Urapmin to abandon their culture and take on an entirely new one, I have found a different outcome in my fieldsite. Initially the Nyaura sought to abandon their own spirits in light of changes in the regional political–economic system brought about by the encounter with white people and due to the devaluation of their spirits by the influence of the Catholic mission. However, when conversion did not bring about a betterment of their living situation as initially hoped, a notion of humiliation returned that led the Nyaura to re‐appropriate their old spirits. Under the influence of a charismatic movement, they discovered that God and His spirits were not new and foreign but old and familiar spirits clothed with new names. Today spirits of the dead are called 'souls', 'saints' and 'angels'; spirits of the bush and water are termed 'nature' that was created by God; and He, the source of everything, is currently re‐interpreted as being the most powerful ancestral spirit there is.